PENDIDIKAN KARAKTER DALAM ISLAM; Kajian dari Aspek Metodologis - Johansyah Johansyah (Universitas Islam Negeri Ar-Raniry, 2011)
Character is the main pillar in promoting the formidable human, either individually or in groups. In Islam, the characters are better known as the akhlaq of the Prophet when he was sent as a delegation of Allah on earth. Based on spirit of the current character education, this paper is to review about how to actual character education in Islam. As matter of fact, character education in Islam is forming in term of akhlakul karimah. Based on the methodological aspect, a method of habituation and exemplary are the best way for character education, which accustom the good thing till considered as culture with the thoughts, feelings and actions. And Examples of good things to students so that transferred the values into their souls, then it will generate a knowledge, as well as manifest in the action